Guide des sources archivistiques sur l'industrie forestière au Nouveau-Brunswick = A Guide to Archival Sources on the New Brunswick Forest Industry. - Nahuet, Robert (Labour / Le Travail, 1991)
The article reviews the book, "Guide des sources archivistiques sur l'industrie forestière au Nouveau-Brunswick = A Guide to Archival Sources on the New Brunswick Forest Industry," by Daniel Hickey, Louise Charlebois, and Bruce Oliver.